A third (meta-)critique - Trakakis, Nick (Sophia, 2006)
I begin my third reply by answering some of the criticisms raised by Tierno against theodical attempts to account for the pervasiveness of moral evil. I then take the discussion to a meta-philosophical level, where I question the very way of thinking about God and evil implicit in Tierno’s critique and in much contemporary philosophy of religion.